REFLECTIVE TEACHING AS A MEANS OF TEACHER PROFESSIONAL DEVELOPMENT - Kurniati, Diah; Nuraeningsih, Nuraeningsih (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
One of the core components of teacher knowledge is reflective knowledge which is defined as the teacher’s capacity to reflect on and assess his or her own practice. In other words, as teachers, they should be able to do reflective teaching. Reflective teaching is the teacher’s thinking about what happens in the classroom lessons, and thinking about alternative means of achieving goals and aims (Cruickshank and Zeichner in Richard and Nunan 1990). This paper discusses reflective teaching as a means of professional development.